2022
DOI: 10.1038/s41409-022-01701-x
|View full text |Cite
|
Sign up to set email alerts
|

Treosulfan plus fludarabine versus TEAM as conditioning treatment before autologous stem cell transplantation for B-cell Non-Hodgkin lymphoma

Abstract: Conditioning with treosulfan and fludarabine (Treo/Flu) has been proven to be feasible and efficient in several types of malignancies before allogeneic hematopoietic stem cell transplantation (allo-HSCT). Given its favorable reduced toxicity profile, we introduced Treo/Flu as conditioning before autologous HSCT (auto-HSCT) in patients with B-cell Non-Hodgkin lymphoma (NHL). The aim of this study was to evaluate the efficacy and safety of Treo/Flu in comparison to TEAM. Fifty-seven patients with NHL received au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…[37][38][39] BCNU replaced by thiotepa as part of TEAM conditioning regimen has promising activity. [20][21][22] However, an observational study described the BEAM protocol to be superior in terms of clinical outcomes, 40 whereas a recent study shows similar results between BEAM and TEAM. 41 We hypothesize that organ dysfunction might play a crucial role in the outcomes of patients undergoing auto-HSCT and only selected patients might profit from TEAM conditioning before auto-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[37][38][39] BCNU replaced by thiotepa as part of TEAM conditioning regimen has promising activity. [20][21][22] However, an observational study described the BEAM protocol to be superior in terms of clinical outcomes, 40 whereas a recent study shows similar results between BEAM and TEAM. 41 We hypothesize that organ dysfunction might play a crucial role in the outcomes of patients undergoing auto-HSCT and only selected patients might profit from TEAM conditioning before auto-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several alternatives to BCNU/carmustine emerged over the years to reduce adverse effects while maintaining the same efficacy 37–39 . BCNU replaced by thiotepa as part of TEAM conditioning regimen has promising activity 20–22 . However, an observational study described the BEAM protocol to be superior in terms of clinical outcomes, 40 whereas a recent study shows similar results between BEAM and TEAM 41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also growing interest in the use of treosulfan as a low-toxicity alternative to busulfan in RIC regimens, and a randomized trial in AML/MDS found that fludarabine-treosulfan (Flu-Treo) was associated with improved NRM and OS compared to Flu-Bu2 ( 88 , 89 ). Preliminary data suggest that Flu-Treo may also be a viable conditioning regimen in NHL ( 90 , 91 ), but confirmation in larger studies is required.…”
Section: Conditioning Regimensmentioning
confidence: 99%